Representasi Unsur-unsur Kebudayaan dalam Legenda Usang Rimau: Kajian Antropologi Sastra - Putri, Eka; Wahyuni, Sri; Sari, Luciana Lidya; Bambang, Siti Enik Mukhoiyaroh (DIKBASTRA: Jurnal Pendidikan Bahasa dan Sastra, 2025)
This research aimed to describe the cultural elements in the legend of Usang Rimau. The method used in this study is a qualitative descriptive method supported by a literary anthropological approach. The source of this research data is the legend of Usang Rimau who comes from South Sumatra Province. This research data is in the form of cultural elements in the legend of Usang Rimau in the form of text quotations in legends. Data collection techniques use documentation and recording techniques used to support this research. The results showed that in the legend of Usang Rimau found as many as seven forms of cultural elements, namely: (1) religious system, (2) community system, (3) knowledge system, (4) language system, (5) living equipment system, (6) living livelihood system, and (7) art. These cultural elements can be used as inspirational and appreciative reading and learning materials as a form of literary appreciation.